2013
DOI: 10.5230/jgc.2013.13.2.111
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Significance of Preoperative Inflammatory Parameters in Gastric Cancer Patients

Abstract: PurposeChronic inflammation induces cancer and cancer induces local tissue damage with systemic inflammation. Therefore, the aim of this study is to investigate the potential relationship between the severity of inflammation and prognosis in cancer patients.Materials and MethodsThis study enrolled 220 patients from January 2002 to December 2006 who underwent gastric surgery. We evaluated the relationship between preoperative inflammatory parameters (erythrocyte sedimentation rate, neutrophil-to-lymphocyte rati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
48
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 15 publications
1
48
0
Order By: Relevance
“…Previous reports have indicated that chronic inflammation may be involved in the development of gastric cancer, since IL-17A and IL-17F are expressed by Th17 cells that mediate chronic inflammation and various diseases (Hu et al, 2013;Lee et al, 2013;Park et al, 2005). Previous studies have investigated the association between rs2275913G>A and rs763780T>C polymorphisms and the risk of gastric cancer, but the results have been inconsistent; therefore, we carried out a meta-analysis to investigate the association to obtain a reliable conclusion.…”
Section: Discussionmentioning
confidence: 97%
“…Previous reports have indicated that chronic inflammation may be involved in the development of gastric cancer, since IL-17A and IL-17F are expressed by Th17 cells that mediate chronic inflammation and various diseases (Hu et al, 2013;Lee et al, 2013;Park et al, 2005). Previous studies have investigated the association between rs2275913G>A and rs763780T>C polymorphisms and the risk of gastric cancer, but the results have been inconsistent; therefore, we carried out a meta-analysis to investigate the association to obtain a reliable conclusion.…”
Section: Discussionmentioning
confidence: 97%
“…Previous reports indicated that chronic inflammation may be involved in the development of gastric cancer, because IL-17A and IL-17F are expressed by Th17 cells which mediate chronic inflammation and various diseases (Park et al, 2005;Hu et al, 2013;Lee et al, 2013). Thus far, some studies have investigated the association between IL-17A and IL-17F polymorphisms and susceptibility to gastric cancer, but the results were unclear.…”
Section: Discussionmentioning
confidence: 99%
“…It is generally known that chronic inflammation can play a critical role in the pathogenesis of gastric cancer (Merchant, 2005;Lee et al, 2013). Previous studies reported that the IL-17 gene is expressed by Th17 cells and modifies chronic inflammation, and SNPs in IL-17 may alter gene expression, thus changing protein function and contributing to cancer risk (Park et al, 2005;Dong et al, 2008).…”
Section: Discussionmentioning
confidence: 99%